THE VIEWS OF PARENTS AND TEACHERS ON THE PROVISION OF ENGLISH LEARNING FOR CHILDREN - Yudha Nur Widiananta; Dadan Rusmana (Journal of English Education and Linguistics, 2021)
This study entitled “The Views of Parents and Teachers on The Provision of English Learning for Children” which aims to reveal the views of parents and teachers about giving English language learning to children. The research method used by the researcher in this study is a qualitative research method by conducting observations and interviews with parents and teachers about giving English language learning to children. The results showed that the majority of parents and teachers strongly agreed with the provision of English learning to children because they experienced a period so that it was easier to understand English lessons compared to adults. Others feel ashamed because the children are still too early to learn the lesson. The provision of English language learning has a positive impact on children in addition to communicating; English can also make children able to compete in the world of work in the future.